Adaptação em Quadrinhos da obra Dom Casmurro como Proposta de Incentivo à Leitura de Machado de Assis. - Santana, Lukas Nascimento (Universidade Federal do Tocantins, 2024)
Classic novels adaptations as graphic novels or comics have become a means for children and teenagers to access the literary canon. In that sense, this work considers the use of adaptations of the novel Dom Casmurro as comics to motivate students to read the work of Machado de Assis. This work is based on theories by Hutcheon (2011), Barbosa et al (2022), Becker (2008) Guimarães et al (2012), among others, that bring us a better understanding of adaptation theory, uses of comics in the classroom, and peculiarities of Machado’s style. Our main objectives are (i) understand the criticism related to adaptation of classics into comics; (ii) debate the use of comics in the High School classroom; (iii) present comics as a genre that can mediate the reading experience of Machado de Assis’s literary original. Three versions of Dom Casmurro as graphic novels were chosen as our object of analysis. The analysis aimed at comparing versions, debating their quality and capacity of promoting the proximity between students and the oeuvre of Machado de Assis.